Accurate experimental determination of gallium K- and L3-shell XRF fundamental parameters. Issue 6 (10th May 2018) - Unterumsberger, Rainer; Hönicke, Philipp; Colaux, Julien L.; Jeynes, Chris; Wansleben, Malte; Müller, Matthias; Beckhoff, Burkhard
Abstract : The fluorescence yield of the K- and L3-shell of gallium was determined using the radiometrically calibrated (reference-free) X-ray fluorescence instrumentation at the BESSY II synchrotron radiation facility. Abstract : The fluorescence yield of the K- and L3-shell of gallium was determined using the radiometrically calibrated (reference-free) X-ray fluorescence instrumentation at the BESSY II synchrotron radiation facility. Simultaneous transmission and fluorescence signals from GaSe foils were obtained, resulting in K- and L3-shell fluorescence yield values ( ω Ga, K = 0.515 ± 0.019, ω Ga, L3 = 0.013 ± 0.001) consistent with existing database values. For the first time, these standard combined uncertainties are obtained from a properly constructed Uncertainty budget. These K-shell fluorescence yield values support Bambynek's semi-empirical compilation from 1972: these and other measurements yield a combined recommended value of ω Ga, K = 0.514 ± 0.010. Using the measured fluorescence yields together with production yields from reference Ga-implanted samples where the quantity of implanted Ga was determined at 1.3% traceable accuracy by Rutherford backscattering spectrometry, the K-shell and L3-subshell photoionization cross sections at selected incident photon energies were also determined and compared critically with the standard databases.